Do NSAID/COX-2 Inhibitors Increase Nonunion After Fracture Surgery? Dilemma and Consideration In Use - Azmi ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: Nonunion accounts for 2% to 10% of fracture complications, diminishing quality of life and increasing mortality risk. Several factors, including smoking, metabolic disorders, dietary inadequacy, and nonsteroidal anti-inflammatory drugs (NSAIDs), may predict nonunion development. NSAIDs are frequently used to treat postoperative pain, including in orthopedic conditions, particularly for fracture pain management. However, NSAID/cyclooxygenase (COX)-2 inhibitor use has been controversial for many years. Many orthopedic surgeons avoid using them in fracture surgery due to their potential adverse effects on osteogenesis and subsequent nonunion risk.Literature Review: An updated literature review was conducted using digital databases such as PubMed, Cochrane, Ovid-SP, Springer Link, and Science Direct, with the search terms "NSAIDs" OR "COX-2 inhibitor" AND "nonunion" AND "fracture surgery." Seven publications that met the inclusion criteria were summarized. This review revealed that while NSAIDs/COX-2 inhibitors have been shown to temporarily inhibit fracture union in some studies, the safety of NSAIDs following fracture fixation without notable interference in bone healing has been demonstrated in others. The association of COX-2 inhibitors or non-selective NSAIDs with nonunion remains unclear.Summary: Prolonged NSAID use interferes with successful bone healing. Short-duration (<2 weeks of treatment) and low-dose NSAID use are considered safe and efficacious for postoperative fracture pain.